"Our Story": Exposition of a Group Support Program for Parents of Children with Developmental Disabilities. Issue 4 (2nd October 2021) - Krstić, Tatjana; Mihić, Ivana; Branković, Jelena
ABSTRACT: Learning about a child's condition and raising a child with a developmental disability can be challenging and emotionally overwhelming, but systematic support programs for parents are practically nonexistent. We find that providing support for parents should be an important public health priority which should be made available through educational, social and healthcare systems. This paper describes a six-week support program for parents of children with developmental disabilities. The program is based on the importance of resolution for providing quality care for the child and for achieving a state of wellbeing for the entire family. Resolution is defined as a process of acceptance and coming to terms with the child's health condition. It refers to the integration of parents' emotions and information regarding their child's disability within the parents' representational system of themselves, their child and their relationship with their child. The main characteristics and goals of this psychoeducational program are highlighted, along with the specific goals for each session. A group setting is applied with the idea that parents will benefit from hearing from people with similar experiences. The structure of all sessions is given in detail and all their components are explained: the introductory section, educational section, counseling section and the final section during which parents are given a handout in which the key content of a particular session is restated. Measures of subjective change and satisfaction with the program are promising, but we intend to further evaluate them in subsequent studies.